2014
DOI: 10.1111/apa.12783
|View full text |Cite
|
Sign up to set email alerts
|

Review of Italian primary care paediatricians identifies 38 commonly prescribed drugs for children

Abstract: Our review of the prescribing habits of family paediatricians showed that 38 commonly prescribed drugs were sufficient to treat most common diseases in children under 15 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Fourth, confounding by indication is a main concern when studying the association between antibiotics and liver injury. Accordingly, the sensitivity analysis in which current exposure to amoxicillin was used as the reference category allowed to control for this potential confounding because amoxicillin is the most frequently used antibiotic in children [31] and is usually considered less hepatotoxic than other antibiotics [25, 32]. Thus, the risk estimate during amoxicillin exposure can be regarded as a proxy of the background risk of liver injury [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, confounding by indication is a main concern when studying the association between antibiotics and liver injury. Accordingly, the sensitivity analysis in which current exposure to amoxicillin was used as the reference category allowed to control for this potential confounding because amoxicillin is the most frequently used antibiotic in children [31] and is usually considered less hepatotoxic than other antibiotics [25, 32]. Thus, the risk estimate during amoxicillin exposure can be regarded as a proxy of the background risk of liver injury [32].…”
Section: Discussionmentioning
confidence: 99%
“…Amoxicillin was chosen since it is the most commonly prescribed antibiotic in children [31] and is considered to be ‘non-hepatotoxic’ when used as a single ingredient compared with its combination with clavulanic acid [15, 32]. …”
Section: Methodsmentioning
confidence: 99%
“…I was interested to read Piovani et al. 's study , which showed that just 38 of the drugs prescribed by Italian primary care paediatricians accounted for 83% of the cartons of the 381 drugs prescribed. These results suggest the need to reflect on how the medical community, health policy makers and representatives of the pharmaceutical industry are involved in prescribing.…”
mentioning
confidence: 99%
“…Nowadays, substantial resources are invested in producing drugs that have similar pharmacological effects, even though those resources could be used for other high‐priority production lines. In addition, a considerable number of medical prescriptions are inappropriate and clinicians face harder decisions as they choose from large number of drugs to treat conditions .…”
mentioning
confidence: 99%
See 1 more Smart Citation